Assessing PT. Bithouse's Priority Strategy In Achieving The Artificial Intelligence Market - Bagus Putu Ardha Krishna Putra; Nyoman Sri Subawa (PT. Publikasiku Academic Solution, 2023)
This research paper aims to explore the managerial strategies adopted by PT. Bithouse, an IT consulting company specializing in AI application development, penetrates the artificial intelligence market in Indonesia. The study employs a qualitative research method to gain in-depth insights into the strategic approaches used by PT. Bithouse. Through interviews, observations, and document analysis, the research seeks to provide a comprehensive understanding of the company's management practices, decision-making processes, and adaptation strategies in the rapidly evolving AI landscape. The findings of this research can contribute to the knowledge and understanding of effective managerial strategies for AI-focused companies operating in emerging markets like Indonesia.